The Mediating Effect of Brand Experience towards the Impact of Social Media Marketing Activities on Enhancing Brand Loyalty in the Case of Tokopedia Indonesia - Jennifer Giovanni Kalinda; Angela Celine Winatali (iBuss Management, 2021)
The social technology era has made social media becoming a tool for marketing strategies that build long-term customer relationships and form brand loyalty. However, recent studies emphasize that customer experience is one of the main issues that marketers must address, thus encouraging marketing executives to switch the strategies that emphasize brand experience. Several scholars mentioned that brand experience would create brand loyalty which social media is the main platform for businesses to foster customer experiences. Due to customer demand for an unforgettable experience that involves pleasant interactions, a company's social media marketing activities must generate excellent brand experiences that will enhance brand loyalty. Therefore, this study aims to understand the impact of social media marketing activities on brand loyalty mediated by brand experience. The object of this research is Tokopedia Indonesia. In this study, data from 96 respondents who have seen Tokopedia social media and have shopped using Tokopedia will be analyzed using multiple linear regression and path analysis in  the IBM SPSS Version 26 program, and a mediation test with bootstrapping using PROCESS 3.5 is performed. The analysis results show that brand experience is proven to have a partial mediation relationship with social media marketing activities on brand loyalty.Keywords:Brand Experience, Social Media Marketing Activities, Brand Loyalty, Tokopedia.Indonesia